2020
DOI: 10.13181/mji.oa.203707
|View full text |Cite
|
Sign up to set email alerts
|

The impact of sleep quality and duration on leptin, appetite, and obesity indices in adults

Abstract: BACKGROUND Poor sleep duration and quality were previously reported to increase the risk of obesity. This study was aimed to evaluate the impact of sleep quality and duration on leptin, appetite, and adiposity in Indonesian adults. METHODS This cross-sectional study recruited adults in Yogyakarta, Indonesia, in 2016. Sleep quality was assessed using the Pittsburgh sleep quality index, appetite was evaluated using the community nutrition appetite questionnaire, and dietary intake was assessed by interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…A study by Wang (2018) explained that short sleep duration could increase a person's appetite due to changes in the secretion of hunger and satiety hormones 36 . Moreover, short sleep duration could also increase a person's tendency to consume unhealthy foods, including sugary drinks, fast food, instant noodles, and confectionery products, and decrease the consumption of vegetables, fruit, and milk 37 . The impact of not following the sleep duration recommendations can increase the size of a person's waist circumference, which is one of the indicators to determine the risk of various cardiovascular diseases 38 .…”
Section: Resultsmentioning
confidence: 99%
“…A study by Wang (2018) explained that short sleep duration could increase a person's appetite due to changes in the secretion of hunger and satiety hormones 36 . Moreover, short sleep duration could also increase a person's tendency to consume unhealthy foods, including sugary drinks, fast food, instant noodles, and confectionery products, and decrease the consumption of vegetables, fruit, and milk 37 . The impact of not following the sleep duration recommendations can increase the size of a person's waist circumference, which is one of the indicators to determine the risk of various cardiovascular diseases 38 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have suggested that poor sleep quality is a risk factor for obesity and being overweight (Abdallah et al, 2021;Muhammad et al, 2020). One of the ways that short sleep duration can lead to obesity is that it is associated with higher energy intake caused by the increased consumption of high-saturated fat food.…”
Section: Introductionmentioning
confidence: 99%